Validation of a diet‐induced Macaca fascicularis model of non‐alcoholic steatohepatitis with dietary and pioglitazone interventions. Issue 4 (17th January 2023) - Camacho, Raul C.; Polidori, David; Chen, Tao; Chen, Bin; Hsu, Helen Han; Gao, Bin; Marella, Mathieu; Lubomirski, Mariusz; Beavers, Traymon; Cabrera, Javier; Wong, Peggy; Nawrocki, Andrea R.
Abstract: Aim: To develop an obese, insulin‐resistant cynomolgus monkey model of non‐alcoholic steatohepatitis (NASH) with fibrosis with a high fat/high cholesterol (HFHC) diet (with or without high fructose) and test its responsiveness to caloric restriction or pioglitazone. Methods: First, two groups of monkeys (n = 24/group) with histologically proven NASH and fibrosis were fed the HFHC diet for 17 weeks. The treatment group was subjected to a 40% caloric restriction (CR) and had their diet switched from the HFHC diet to a chow diet (DSCR). Paired liver biopsies were taken before and 17 weeks after DSCR. Subsets of monkeys (nine/group) had whole liver fat content assessed by MRI. Next, two groups of monkeys with histologically proven NASH and fibrosis were treated with vehicle (n = 9) or pioglitazone (n = 20) over 24 weeks. Results: The HFHC and DSCR groups lost 0.9% and 11.4% of body weight, respectively. After 17 weeks, non‐alcoholic fatty liver disease activity score (NAS) improvement was observed in 66.7% of the DSCR group versus 12.5% of the HFHC group ( P  < .001). Hepatic fat was reduced to 5.2% in the DSCR group versus 23.0% in the HFHC group ( P  = .0001). After 24 weeks, NAS improvement was seen in 30% of the pioglitazone group versus 0% of the vehicle group ( P  = .08). Conclusions: Both weight loss induced by DSCR and treatment with pioglitazone improve the histological features of NASH in a diet‐induced cynomolgus monkey model. This model provides a translational preclinical model for testing novel NASH therapies.